Identification and Characterization of Pure Sleep Epilepsy in a Cohort of Patients With a First Seizure. (3rd May 2022) - Pang, Elaine; Lawn, Nicholas; Lee, Judy; Dunne, John
Abstract : Background and Objectives: Our aim was to study the development of pure sleep epilepsy after a first-ever seizure from sleep in adults. Methods: This was a prospective observational study of patients seen at a tertiary hospital–based first seizure clinic between 2000 and 2011. Adults with a first-ever unprovoked seizure from sleep were consecutively recruited. All patients were followed up at least once after the initial seizure, and those not requiring regular clinical review were contacted every 1 to 2 years. The timing and pattern of subsequent seizures and potential predictors of future awake seizures were analyzed. Results: Two hundred thirty-nine adults with a first-ever unprovoked seizure from sleep were identified. Sixty-one percent were male; mean age was 43 years (range 14–88 years); and median follow-up of 8.8 years (range 2 months–18 years). Of the 174 patients who had recurrent seizures, 130 patients (75%) had their second seizure from sleep, and of these, 76 of 94 (81%) also had their third seizure from sleep. Eighty-nine patients (37%) developed awake seizures during follow-up. In half of these patients, the awake seizure occurred within 2 years of the initial seizure. The risk of an awake seizure within 1 year of a first-ever seizure from sleep was 13.9% (95% CI 9.4%–18.3%), falling to 2.0% to 5.3% per year after 3 years. The risks of an awake seizure within 1 year of a second or third consecutive sleep seizure were 9.9% (95% CI 4.6%–15.3%) and 8.7% (95% CI 2.0%–15.4%), respectively, and similarly decreased with time. Discussion: Most initial seizure recurrences after a first-ever sleep seizure occur during sleep. While more than one-third eventually had awake seizures, the annual risk of an awake seizure was ≤14% and decreased with time, albeit with a small ongoing risk of between 2% and 5% per year. These findings may be used in counseling patients with seizures from sleep and to inform driving recommendations.